2000
DOI: 10.1007/s004249900189
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, ATP and nuclear pore channel gating

Abstract: Nuclear envelope (NE) cisternal Ca 2+ and cytosolic ATP are required for nuclear-pore-complex-(NPC-) mediated transport of DNAs, RNAs, transcription factors and other large molecules. Isolated cardiomyocyte nuclei, capable of macromolecular transport (MMT), have intrinsic NPC ion channel behavior. The large ion conductance (γ) activity of the NPC channel (NPCC) is blocked by the NPC monoclonal antibody mAb414, known to block MMT, and is also silenced during periods of MMT. In cardiomyocytes, neither cytosolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…The latter maintain the membrane potential at hyperpolarizing potentials and the driving force for Cl Ϫ efflux thereby ensuring efficient ion and water movement (12) (32)(33)(34)(35). Several reports have suggested that these observations are due to modulation of the nuclear pore complex (36,37), differential nuclear Ca 2ϩ buffering (35,38), or even nuclear dye artifacts (17). Although we cannot completely rule out these effects, an important observation from the present study is that inhibition of mitochondrial Ca 2ϩ uptake completely abolishes the nuclear [Ca 2ϩ ] delay.…”
Section: Discussionmentioning
confidence: 99%
“…The latter maintain the membrane potential at hyperpolarizing potentials and the driving force for Cl Ϫ efflux thereby ensuring efficient ion and water movement (12) (32)(33)(34)(35). Several reports have suggested that these observations are due to modulation of the nuclear pore complex (36,37), differential nuclear Ca 2ϩ buffering (35,38), or even nuclear dye artifacts (17). Although we cannot completely rule out these effects, an important observation from the present study is that inhibition of mitochondrial Ca 2ϩ uptake completely abolishes the nuclear [Ca 2ϩ ] delay.…”
Section: Discussionmentioning
confidence: 99%
“…However, quantitative comparison of structural AFM data with the functional NEER experiments indicates that most likely a certain percentage of NPCs (about 20%) become electrically tight for a short period (a few minutes) and then are again open for inorganic ion movements. A similar model was developed by Bustamante and coworkers (14,36) applying patch-clamp techniques to the NE. The early NEER peak was followed by a marked decrease in the envelope resistance.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the details for the new preparation, the experiments followed procedures developed earlier [5,10,11,12]. Briefly, the experiments consisted of monitoring with fluorescence microscopy the expression of enhanced GFP (EGFP) plasmids and the nuclear translocation of various fluorescent probes (e.g.…”
Section: Methodsmentioning
confidence: 99%